2007
DOI: 10.1523/jneurosci.3477-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sef Levels Influence Auditory Brainstem Development and Function

Abstract: During development of the CNS, secreted morphogens of the fibroblast growth factor (FGF) family have multiple effects on cell division, migration, and survival depending on where, when, and how much FGF signal is received. The consequences of misregulating the FGF pathway were studied in a mouse with decreased levels of the FGF antagonist Sef. To uncover effects in the nervous system, we focused on the auditory system, which is accessible to physiological analysis. We found that the mitogen-activated protein k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 62 publications
6
25
0
Order By: Relevance
“…S1a). Il17rd − / − pups were born in an expected Mendelian ratio and showed no obvious phenotypic abnormalities and this is consistent with previously generated IL-17RD-deficient mice 25 . As expected, Il17rd mRNA expression is abolished in Il17rd − / − mice and replaced by β-Geo expression ( Supplementary Fig.…”
Section: Il-17rd Differentially Regulates Il-17a-responsive Genessupporting
confidence: 91%
“…S1a). Il17rd − / − pups were born in an expected Mendelian ratio and showed no obvious phenotypic abnormalities and this is consistent with previously generated IL-17RD-deficient mice 25 . As expected, Il17rd mRNA expression is abolished in Il17rd − / − mice and replaced by β-Geo expression ( Supplementary Fig.…”
Section: Il-17rd Differentially Regulates Il-17a-responsive Genessupporting
confidence: 91%
“…The staining pattern by immunohistochemistry matches the expected distribution of GFAP in mouse auditory brainstem (Abraira et al, 2007). With the use of cultured mouse primary astrocytes, the antibody staining demonstrates a filamentous pattern, consistent with GFAP presence in intermediate filaments.…”
Section: Glial Fibrillary Acidic Protein (Gfap) Antibodysupporting
confidence: 67%
“…ABR measurements have proven to be a robust method for analyzing the effects of genetic mutations on hearing in mice, both in mutagenesis screens (Kermany et al, 2006) and in the evaluation of candidate genes (Abraira et al, 2007;Blauwkamp et al, 2007;Polley et al, 2006). In these studies, the candidate genes are transcription factors or morphogens with identified roles in nervous system development.…”
Section: Discussionmentioning
confidence: 99%